Accelerated Learning Programmes: What can we learn from them about curriculum reform? - Longden, Ken (UNICEF, 2013)
The purpose of this paper is to present a cross-country analysis of the content and implementation of successful Accelerated Learning Programmes, ALPs. A literature search was conducted to find information on as many ALPs, as possible. This resulted in a matrix displaying key features of ALPs. Using the information from fifteen ALPs where almost complete data was available, an analysis was undertaken to discern the nature of these programmes in terms of providing improved access to learning. Five ALPs covering a range of types were selected for more detailed study. Finally, the lessons learned from ALPs were highlighted; potential implications for reform in the formal system were discussed with particular emphasis on the curriculum and teacher education.
KerkoCite.ItemAlsoKnownAs: 2339240:NDS4HXFZ 2405685:GUAFHF4Y 2405685:N3L7U5B2
Keywords: ⛔ No DOI found